From Identity to Ambugity: Exploring Interprofessional Collaboration Opportunities for Pharmacists in Rural and Remote Australia - Selina Taylor; Alannah Franich; Sophie Jones; Beverley D. Glass (Pharmacy, 2023)
Rural and remote populations are predisposed to poorer health outcomes, largely associated with limited access to health services and health professionals. This disparity provides an opportunity for health professionals to work collaboratively in interdisciplinary teams to deliver improved health outcomes for rural and remote communities. This study aims to explore exercise physiologist and podiatrist perceptions of interprofessional practice opportunities with pharmacists. Role theory provided a framework for this qualitative study. Interviews were conducted, recorded, transcribed, and thematically analysed according to the constructs of role theory (role identity, role sufficiency, role overload, role conflict, and role ambiguity). The perceptions of participants varied, largely due to the lack of understanding of the role and scope of the practice of a pharmacist. Participants acknowledged and adopted a flexible approach to the way in which they delivered health services to meet the needs of the community. They also described a more “generalist” approach to care, owing to the high prevalence of disease and disease complexity, along with a lack of staffing and resources. The potential for increased interprofessional collaboration was supported and identified as a strategy to manage significant workloads and provide improved patient healthcare. The application of role theory to this qualitative study provides insight into perceptions of interprofessional practice that may inform future development of remote practice models of care.